Disinformation persuasion effects of disinformation articles on the cognition, attitudes, and behaviors of filipinos - Espaldon, Allyson Mae F.; Glova, Nelfa M. (2019)
With the rampant spread of fake news in the Philippines, this pretest-posttest quasi-experimental study used the Elaboration Likelihood Model (ELM), aided with the Cognitive Dissonance Theory (CDT), and Psychological Reactance Theory to investigate the persuasion effects of disinformation articles online in relation to the demographic factors and political partisanship of the participants (n=60) by tracing their information processing routes. The study is comprised of two (2) stages: in the first stage, the participants were asked to read a pre-elected disinformation article titled, Korina Sanchez, matapang na binatikos and power nap ng Pangulo sa Singapore and the second stage consisted of a 51-item Likert-type scale questionnaire assessing the disinformation article. The participants used the parallel route of information processing rather than the purely central route or peripheral route as they found the article to be highly attractive and highly credible. It was also found out that the participants appropriated the dissonant information with their preexisting ideas and beliefs when they experienced dissonance as most of them supported President Duterte and Duterte-endorsed candidates in the last 2019 elections. With the participants finding the disinformation article highly credible and persuasive, this study highlights the importance of fact-checking organizations in combating the spread of fake news in the Philippines as participants cannot differentiate disinformation articles from legitimate news articles without cues.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019